Exploring Wireless Time-Sensitive Networking and QoS in V2X Scenarios - Aguiar, Gabriel De O.; Gracioli, Giovani (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2025)
Safety-Critical V2X maneuvers—platooning, coordinated braking, distributed sensing—collapse when wireless delay jitter flares or one talkative node monopolizes the communication channel. Commodity Wi-Fi provides neither determinism nor per-station fairness. We address both issues with two lightweight Time-Aware Shaper (TAS) schedules that carve each cycle into eight fixed, non-overlapping slots, reserving gaps for best-effort traffic. The design relies only on coarse IEEE 802.1AS synchronization—eschewing full 802.1Qbv gate lists—so it fits embedded on-board units. We implement the shapers in OMNET++ 6.1/INET 4.5.2 and evaluate eight vehicles at motorway speed while deliberately stressing their clocks.The tighter-cycle variant (TAS2, Tcycle = 48 ms, Tslot = 6 ms) slashes the end-to-end delay coefficient-of-variation from 177% (EDCA) to 63%, holds mean delay at 22 ms, and enforces the desired 0.125 RPHY bandwidth cap per vehicle with only a 3.1% aggregate-throughput penalty versus an unconstrained baseline. These results show that simple static slotting—not complex per-packet scheduling—can deliver deterministic latency and predictable per-car capacity on off-the-shelf Wi-Fi, making wireless TSN a viable foundation for next-generation cooperative vehicular systems.